Transparency in the assessment of Takaful claims for construction works loss & damage - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (Universiti Sultan Azlan Shah, 2016)
In the context of the construction industry, an alternative to the conventional insurance for works contracts is the Shariah compliant insurance otherwise known as takaful. Among the most frequently used takaful for construction works contracts is the Contractor’s All Risks (CAR) Takaful. However, the future of CAR Takaful may be affected should issues such as marketing and clarification on how it works including how claims are processed, valued and compensation made are not made know to Contractors and Clients. In fact, previous studies have identified that issues on transparency in CAR Takaful products is among the major concerns expressed by the Contractors and Clients. Consequently, a study was conducted, the key objectives being to establish understanding on the concept of transparency in CAR Takaful claims and assess, from the perspectives of the Contractors and Clients, on whether the dealings in CAR Takaful claims are considered transparent or otherwise. The study was conducted principally via desk research and interviews with representative from takaful operators, Contractors and Clients organizations. Key results from the study suggest that transparency in CAR Takaful dealings is a concern especially those related to compliance with the Shariah and manner in which claims are valued and compensation decided. Such lack of transparency, if not addressed soonest possible, may not augur well for the future of the CAR Takaful industry.